Red‐emitting CaSc2O4:Eu3+ phosphor for NUV‐based warm white LEDs: structural elucidation and Hirshfeld surface analysis. (2nd June 2020) - Shaishta, Naghma; Khan, Waheed Ullah; Mane, Sunil Kumar Baburao; Hayat, Asif; Zhou, Dong‐Dong; Khan, Javid; Mehmood, Nasir; Inamdar, Hajeebaba K; Manjunatha, G.
Summary: We have prepared Eu 3+ activated phosphor from the host CaSc2 O4 (CSO) via high‐temperature facial solid‐state route and characterized by various spectral techniques. Surface morphology and composition was determined via scanning electron microscope (SEM) and X‐ray energy dispersive spectroscopy (EDAX). The crystal structure refinements show the Pnam 62 space group with two active centres for Eu 3+ in the prepared CSO:Eu 3+ phosphor. Additionally, first time the detailed investigation of intermolecular interactions through Hirshfeld surface (HSs) analysis for the inorganic phosphor has been reported, the analysis indicates that the Sc/EuO and CaO contacts in the CSO:Eu 3+ crystal account for more than 60% and 26% of the total HSs area. The synthesized phosphor shows an intense red emission at 618 nm (Ex 394 nm) with a CIE coordinates of (0.633, 0.358) and measured internal quantum efficiency (IQE) was found to be 84%. Further, correlated colour temperature was estimated to be about 6049 K including colour purity of 93.04% for Eu = 0.10 and the thermal stability were established by their temperature dependent study (400 K = 92%). Therefore, the phosphor of CSO:Eu 3+ exhibits a potential application for UV‐based warm white LEDs and in the determination of intermolecular interactions through HSs surface analysis studies.